1996
DOI: 10.1144/gsl.sp.1996.106.01.18
|View full text |Cite
|
Sign up to set email alerts
|

Role of pre-Tertiary fractures in formation and development of the Malay and Penyu basins

Abstract: Major faults in Sundaland trend NNW to NW, WNW, N and E. Some of the NNW to NW and N-striking faults across Mesozoic areas of the Malay Peninsula were active until mid-Eocene time. Small, fault-bounded Tertiary basins onshore may be pull-apart basins associated with such faults. Mainly from seismic data, NNW to NW, N and E-striking faults have been recognized in the pre-Tertiary basement of the Malay and Penyu basins off the east coast of the peninsula. These faults were reactivated before the Late Oligocene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…Left-lateral shear during the late Eocene to Oligocene formed pull-apart basins and half grabens into which thick sedimentary sequences were deposited (Ngah andothers 1996, andTjia andLiew, 1996). Expulsion of portions of continental Southeast Asia resulted from collision between the India plate and the Eurasia plate in the midEocene (Tjia, 1994, andNgah andothers, 1996).…”
Section: Exploration Historymentioning
confidence: 99%
See 3 more Smart Citations
“…Left-lateral shear during the late Eocene to Oligocene formed pull-apart basins and half grabens into which thick sedimentary sequences were deposited (Ngah andothers 1996, andTjia andLiew, 1996). Expulsion of portions of continental Southeast Asia resulted from collision between the India plate and the Eurasia plate in the midEocene (Tjia, 1994, andNgah andothers, 1996).…”
Section: Exploration Historymentioning
confidence: 99%
“…Expulsion of portions of continental Southeast Asia resulted from collision between the India plate and the Eurasia plate in the midEocene (Tjia, 1994, andNgah andothers, 1996). This expulsion produced left-lateral shear on a southeastern extension of the Three Pagoda fault zone in the Malay Basin (a major fault system onshore Thailand) (Tjia, 1994;Ngah and others, 1996;Mazlan B. Hj.…”
Section: Exploration Historymentioning
confidence: 99%
See 2 more Smart Citations
“…Thermochronological analysis of granitic rocks of the Malay Peninsula shows several periods of exhumation, during Late Cretaceous to early Paleogene and Eocene 45,47 . The Late Eocene to Oligocene rapid exhumation coincides with significant subsidence in offshore areas 47 , during the time when sinistral transtensional movement along pre-existing NW-SE fault zones formed the Tertiary offshore and onshore basins [51][52][53] . From this study, it is shown that the Bok Bak fault underwent an early brittle-ductile dextral strike-slip, possibly initiated as early as Late Jurassic, with the fault undergoing cooling during Early Cretaceous.…”
mentioning
confidence: 99%